Research on Delayed-feedback Compensation of Pneumatic Position Sensor in Hot Cell - ZHOU Keyuan1, DONG Jianpeng2, DONG Bibo1, YANG He1, XIANG Routong2 (Yuanzineng kexue jishu)
The various types of radiation in the hot cell (irradiation atmospheres) can seriously affect the service life of electronic components. Therefore, a pneumatic position sensor that can be applied in irradiation conditions based on the non-contact pneumatic position sensor is proposed in this paper. The sensor separates the signal processing part and the sensing part. During the working process, the sensing part perceives the position information of the workpiece and transmits the signal to the processing part through the gas circuit. If the pressure signal at the processing part shows an expected change, it can be determined that the workpiece (such as spent fuel assembly) has reached the designated position. Due to the compressibility of gas, there is a signal delayed-feedback phenomenon in pneumatic position sensors. To improve the above issues, the flow field inside the sensor was decomposed into pipes and valve switches for flow characteristic analysis. A model of the internal fluid domain of the valve switch was established. The relationship between the flow rate and pressure ratio of the valve switch under different opening degrees was obtained, and then the influence of valve openings on the critical pressure ratio and sonic conductance of gas flow was elucidated. Based on the assumption that the gas medium was ideal air and the flow inside pipes was single-phase, the internal flow field model of pipes was derived. The method of characteristics was used to numerically solve the above mentioned model, and the influence of pipe diameter and pipe length on the flow characteristics were analyzed. The results show that the sonic conductance and the critical pressure ratio of air flow are positively correlated with pipe diameter and negatively correlated with pipe length. The pressure response prediction model of the sensor was constructed and the hysteresis was calculated. The compensation strategy for signal delayed-feedback was proposed based on the hysteresis. Finally, a pneumatic position sensor response detection platform was built to verify the effectiveness of the prediction model. The platform mainly consistsed of four modules, namely servo drive system, slider mechanism, measurement and control system, and sensor part. The compensation verification of pneumatic position sensors was carried out under two different working conditions. The prediction model has good consistency with the actual pressure response curve, and the accuracy after compensation is significantly improved. The maximum difference between the compensated position and the expected value does not exceed 0.5 mm, which can meet the requirements of practical engineering applications and verifies the effectiveness of the compensation strategy.